Biology of fall armyworm (Spodoptera frugiperda) infesting sugarbeet (Beta vulgaris) - M, SHANTHI; T K, NIVETHA; A V, MOORTHY; G, SRINIVASAN; A, GURUSAMY (The Indian Journal of Agricultural Sciences, 2024)
The potential for damage caused by the maize fall armyworm (FAW) varies considerably, ranging from 9.0–62.5% across different seasons and regions in India. This poses a significant threat to the food and nutritional security of numerous farmers in the country. Notably, the FAW has been identified as a new host for sugarbeet, marking the first instance of such an occurrence. A comprehensive examination of the fall armyworm's behaviour in this new host was conducted. The infestation of the FAW in sugarbeet commenced during the seedling stage and persisted until the harvesting phase. During the initial seedling stage, larvae within the rhizosphere region induced defoliation of leaves and inflicted damage to the collar region. This led to the drying of the central shoot, mirroring the symptoms of dead heart, although no scraping symptoms were observed. As the plants entered the vegetative stage, they experienced further defoliation and wilting. In terms of its life cycle, the FAW exhibited distinct stages. The egg stage lasted around 3.2 ± 0.17 days. Larvae generally underwent 6 instars, with durations of 3.8 ± 0.65 days, 3.2 ± 0.90 days, 2.9 ± 0.14 days, 3.1 ± 0.36 days, 3.6 ± 0.24 days, and 6.8 ± 0.74 days for the first to sixth instars, respectively. The overall larval period ranged from 19 to 25 days, with an average of 23.4 ± 3.20 days. The pupal and adult stages lasted approximately 9.3 ± 1.80 days and 11.1 ± 1.94 days, respectively. Consequently, the complete life cycle of the fall armyworm in the sugarbeet, as observed under laboratory conditions, spanned approximately 43.8 ± 6.94 days.